Multiple Iterations of Magnetic Resonance-Guided Laser Interstitial Thermal Ablation of Brain Metastases: Single Surgeon's Experience and Review of the Literature. Issue 2 (12th December 2019) - Eichberg, Daniel G; Menaker, Simon A; Jermakowicz, Walter J; Shah, Ashish H; Luther, Evan M; Jamshidi, Aria M; Semonche, Alexa M; Di, Long; Komotar, Ricardo J; Ivan, Michael E
Abstract: BACKGROUND: Prior treatment with magnetic resonance-guided, laser-induced thermal therapy (LITT) is widely assumed not to be a contraindication for further treatment of brain lesions, including further iterations of LITT. However, the safety and efficacy of repeat LITT treatments have never been formally investigated. OBJECTIVE: To evaluate treatment with multiple iterations of LITT. METHODS: All patients treated with LITT at least twice at our institution were included in the study. Outcomes and neurological examinations from before and after surgery were retrospectively examined from clinic notes. Perilesonal edema was determined at various timepoints using volumetric data derived from manual tracings of fluid-attenuated inversion recovery (FLAIR) enhancement on magnetic resonance imaging (MRI). Finally, a literature review of prior cases of repeat LITT was performed. RESULTS: A total of 9 patients underwent 18 treatments with LITT; all but 1 of whom were treated for metastatic brain lesions. One patient had a transient cerebrospinal fluid leak, whereas a second patient had a superficial wound infection, both of which resolved with standard medical care. The remaining 7 patients tolerated all LITT procedures without complication. Analysis of perilesional edema volume demonstrated a correlation with the amount of energy delivered during LITT. Literature review found 5 published papers describing 9 patients who underwent LITT more than once, the majority of whom tolerated repeat LITT well. CONCLUSION: LITT is a safe and promising treatment modality and may be used multiple times without issue. There appears to be an association between the amount of energy delivered during a LITT session and the degree of postoperative perilesional edema.